Plant chemical biology - Audenaert, Dominique, 1976-; Overvoorde, Paul, 1968- (Hoboken, New Jersey : John Wiley & Sons Inc., 2014)
"The application of plant chemical biology is currently limited to specialized subfields of plant research. By examining how chemical biology can be applied to study plant biology, Plant Chemical Biology illustrates how chemical biology is a means to identify small molecules that can be used to identify the targets of currently used herbicides, as well as to develop new herbicides or plant growth regulators. The author introduces researchers and graduate students to the chemical biology toolbox required to perform successful chemical biology studies. The text also examines several chemical biology studies to show how they allowed novel insights into the field of plant physiology and plant cellular processes"--Provided by publisher.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Botanical chemistry; Plants -- chemistry; Biochemical Phenomena; Plant Physiological Phenomena; SCIENCE -- Life Sciences -- Biochemistry; Botanical chemistry; Electronic books; Electronic books